Marrow adipogenesis and bone loss that parallels estrogen deficiency is slowed by low-intensity mechanical signals. Issue 2 (February 2016) - Krishnamoorthy, D.; Frechette, D.; Adler, B.; Green, D.; Chan, M.; Rubin, C.
Abstract Summary Ovariectomized mice were used to assess the ability of low-intensity vibrations to protect bone microarchitecture and marrow composition. Results indicate that low-intensity vibrations (LIV), introduced 2 weeks postsurgery, slows marrow adipogenesis in OVX mice but does not restore the bone within the period studied. However, immediate application of LIV partially protects quality. Introduction The aim of this study was to evaluate consequences of estrogen depletion on bone marrow (BM) phenotype and bone microarchitecture, and effects of mechanical signals delivered as LIV on modulating these changes. Methods LIV (0.3 g, 90 Hz) was applied to C57BL/6 mice immediately following ovariectomy or 2 weeks postestrogen withdrawal for 2 (ST-LIV) or 6 weeks (LT-LIV), respectively. Sham-operated age-matched controls (ST-AC, LT-AC) and ovariectomized controls (ST-OVX, LT-OVX) received sham LIV treatment. Bone microstructure was evaluated through μCT and BM adipogenesis through histomorphometry, serum markers, and genes expression analysis. Results LT- OVX increased BM adipogenesis relative to LT-AC (+136 %, p ≤ 0.05), while LT-LIV introduced for 6w suppressed this adipose encroachment (−55 %, p ≤ 0.05). In parallel with the fatty marrow, LT-OVX showed a marked loss of trabecular bone, −40 % (p ≤ 0.05) in the first 2 weeks following ovariectomy compared to LT-AC. Application of LT-LIV for 6w following this initial 2w bone loss failed to restore the lost trabeculae but did initiate an anabolic response as indicated by increased serum alkaline phosphatase (+26 %, p ≤ 0.05). In contrast, application of LIVimmediately following ovariectomy was more efficacious in the protection of trabecular bone, with a +29 % (p > 0.05) greater BV/TV compared to ST-OVX at the 2w time period. Conclusions LIV can mitigate adipocyte accumulation in OVX marrow and protect it by favoring osteoblastogenesis over adipogenesis. These data also emphasize the rapidity of bone loss with OVX and provide perspective in the timing of treatments for postmenopausal osteoporosis where sooner is better than later.